Ergonomic weighted scores to evaluate critical instructions for improvements in a printed circuit assembly factory - Sen, Rabindra Nath; Yeow, Paul H.P. (2003)
A survey was conducted on the efficacy of the Printed Circuit Assembly operations using newly designed Ergonomic Weighted Scores (EWSs) to evaluate Critical Instructions (CIs) to operators. This helped to choose priorities of problematic operations. Five EWSs were drafted, tried, and finalized by a team of experts, for the purpose of checking the adherence to CIs, failing any of which could cause adverse effects on the quality of products. The top three priority operations were identified and the follow-up studies resulted in an increase in monthly revenue of US$227,880 and improvements in quality, productivity, occupational health and safety of the operators. (C) 2003 Wiley Periodicals, Inc.